The role of zakat distribution on the sustainability of gharimin (genuine debtors) in Islamic financial institutions in Malaysia - Yamaludin, Siti Mazlita; Syed Alwi, Sharifah Faigah; Rosman, Romzie; Khamis, Mohd Rahim (Emerald Publishing, 2024)
Purpose – This study aims to explore the COVID-19 impact on the sustainability of gharimin (genuine debtors) in Islamic financial institutions (IFI) in Malaysia. The analysis was further conducted to expand the interpretation of gharimin in zakat institutions (ZI) to use the role of zakat distribution during the postpandemic period due to income shock and long-term unemployment. Design/methodology/approach – This study adopted a qualitative research approach with grounded theory analysis to integrate theoretical insights into the interpretation of gharimin and current practices from the perspectives of ZI and IFI. An in-depth interview with 18 informants was conducted, and data were collected from senior management positions in the zakat distribution department, academicians who are experts in the area of zakat, and heads of Shariah departments in IFI. Findings – Expanding the interpretation of gharimin could help ZI and IFI recover the sustainability of gharimin for preparedness during post-pandemic and any emergency crisis in the future. Practical implications – This study implies the potential role of ZI in combating the risk of defaulting debtors in IFI to prepare for pandemic recovery in the future. Social implications – The new interpretation assists gharimin in reducing the burden debt using the zakat fund and protects genuine debtors by preventing IFI from declaring default or bankruptcy. Originality/value – This study narrows the literature gaps about gharimin in IFI in the context of the pandemic. To the best of the authors’ knowledge, this is, perhaps, the first paper to present the expansion of interpretation for gharimin into mu’sir in IFI in Malaysia